Índices fisiológicos e crescimento inicial de mamoeiro (Carica papaya L.) em casa de vegetação - Lima, Juliana Firmino de (2007)
In Brazil, the papaya crop (Carica papaya L.) is well diffused, specially in the Southern Region of the State of Bahia and the Northern Region of the State of Espírito Santo, where most of the commercial plantations are concentrated. Papaya is a crop that needs renovation of the orchards every four years, at the most, demanding the development of new technologies and improvement in the quality of the plantlets, also demanding the development of research in this area. Growth analysis has been used by researchers in order to explain growth differences of genetic or environmental causes. This is a very efficient tool for the identification of promising materials and characteristics that possibly increase the yield of abolt plant during the initial growth, favoring the works of breeding. This is valmble infermatian for plant breeding army productive. The objective of the present work was to evaluate the initial growth of papaya plants growing under greenhouse conditions using physiological indexes as yield indicative parameters. Therefore, a complete randomized block experiment was carried out using the Golden cultivar and the Tainung Nº1 hybrid. It was concluded that the physiological indexes: absolute growth ratio, relative growth ratio, accurate assimilation ratio and leaf area ratio are efficient tools to identity and compare different genetic materials during the initial growth of papaya plants growing under greenhouse conditions.